Conductive Atomic Force Microscopy Study of the Resistive Switching in Yttria-Stabilized Zirconia Films with Au Nanoparticles. (2nd July 2018) - Filatov, Dmitry; Kazantseva, Inga; Antonov, Dmitry; Antonov, Ivan; Shenina, Maria; Pavlov, Dmitry; Gorshkov, Oleg
Abstract : We report on the investigation of the resistive switching (RS) in the ultrathin (≈5 nm in thickness) yttria-stabilized zirconia (YSZ) films with single layers of Au nanoparticles (NPs) by conductive atomic force microscopy (CAFM). Besides the butterfly-type hysteresis loops in the current-voltage (I -V ) curves of the contact of the CAFM probe to the investigated film surface corresponding to the bipolar RS, the negative differential resistance (NDR) has been observed in theI -V curves of the AFM probe contact to the YSZ films with Au NPs in the conductive ("ON") state. The NDR has been related to the resonant tunneling of electrons through the size-quantized energy states in the ultrafine (1 to 2 nm in diameter) Au NPs built in the conductive filaments in the YSZ films.